Mentawai Tribe's Natural Disaster Mitigation Model Through Local Wisdom - Dewi Rahmadani Siregar; Eri Barlian; Indang Dewata; Nurhasan Syah (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to identify and analyze mitigation and adaptation to natural disasters carried out by the Mentawai tribe. This study uses a qualitative research type with an ethnographic approach. Determination of informants in this study used the snowball sampling method, a sampling technique that starts with a small number then develops along with the data collection process. Data collection techniques: direct observation in the field, interviews, documentation, and literature studies. Data analysis was carried out through the stages of data collection, data reduction, data presentation, and drawing conclusions. Results of this study indicate that there are two models of natural disaster mitigation based on local wisdom, namely the stilt house (Uma) which is located in coastal communities and arat sabulungan which is located in hilly communities. Local wisdom of Uma which is located in coastal areas is used and trusted for mitigating earthquakes, tsunamis and floods. Local wisdom of arat sabulungan for mitigating landslides in the Mentawai hills. This study also shows structural adaptation strategies, socio-cultural adaptation and economic adaptation of the community in dealing with natural disasters in the Mentawai Islands region. Conclusion is that with local wisdom, communities are able to maintain the existence of their lives.